(untitled) (International Journal of Management and Sustainability, 2014)
This study is set out to analyze the Configuration (behavior) of Nigerian firms’ export marketing in the global market. This can be appreciated from the fact that export play important role in the socio-economic development of nations; in the areas of value creation and facilitate economics of abundance for national development. The data were generated through structured questionnaire administered on sixty exporting firms located in Lagos. The data were statistically subjected to T-tests, employing Analysis of Variance (ANOVA), in Special Packages for Social Sciences (SPSS). The findings revealed that Nigerian exporting firms are patterned into Experimental, Active, and Committed. The findings also showed that Nigeria firms’ years of export involvement influence their pattern of export, just as company size and number of employee’s impact on firms’ categorization of export involvement. The findings of this study are peculiar because it focuses on Nigeria firms involved in export, and give valuable insight on the prospects and challenges on pattern of Nigerian firms’ marketing activities in the global market. Nigeria’s desire to attain the economic vision of 202020 (being among 20 top Global Economies in the Year 2020) will be enhanced and achieved; if the findings of this study are professionally and sincerely pursued, and what it can contribute to the nation’s development is positively considered by stakeholders.